2021
DOI: 10.1038/s41467-021-22152-w
|View full text |Cite
|
Sign up to set email alerts
|

Pili allow dominant marine cyanobacteria to avoid sinking and evade predation

Abstract: How oligotrophic marine cyanobacteria position themselves in the water column is currently unknown. The current paradigm is that these organisms avoid sinking due to their reduced size and passive drift within currents. Here, we show that one in four picocyanobacteria encode a type IV pilus which allows these organisms to increase drag and remain suspended at optimal positions in the water column, as well as evade predation by grazers. The evolution of this sophisticated floatation mechanism in these purely pl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 54 publications
4
26
0
Order By: Relevance
“…Other structures tied to the cell surface are extracellular appendages such as the pili [ 37 ] and the spinae [ 38 ]. The type IV pili are appendages that can be extended and retracted, not only for motility or to attach to a surface and form a biofilm, but also to float in planktonic lifestyles and to avoid predation [ 39 ]. The spinae are rigid tubes from 100 nm to 1 µm long that can induce microcolony formation in freshwater Cyanobium sp.…”
Section: The Genus Synechococcusmentioning
confidence: 99%
“…Other structures tied to the cell surface are extracellular appendages such as the pili [ 37 ] and the spinae [ 38 ]. The type IV pili are appendages that can be extended and retracted, not only for motility or to attach to a surface and form a biofilm, but also to float in planktonic lifestyles and to avoid predation [ 39 ]. The spinae are rigid tubes from 100 nm to 1 µm long that can induce microcolony formation in freshwater Cyanobium sp.…”
Section: The Genus Synechococcusmentioning
confidence: 99%
“…This wide distribution suggests that type IV pili could be the apparatus that drives gliding motility in all cyanobacteria, however, in filamentous species belonging to the Oscillatoriales order [ 7 ] the role of type IV pili has as yet not been analyzed and other mechanisms for movement have been proposed [ 25 ]. Besides gliding movement and DNA uptake, other functions have been described in cyanobacteria in which type IV pili are involved, such as flocculation [ 20 ] or floating in water column [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…4A). To test whether the damage to HlyBD‐TolC system cause cell sedimentation, the typical phenotype of the mutant of type IV pili and extracellular polysaccharide (Jittawuttipoka et al ., 2013; Flores et al ., 2019; Aguilo‐Ferretjans et al ., 2021), an experiment of motionless incubation for 18 days was conducted. The results showed that the cultures of the ∆ hlyB , and ∆ slyA mutants and the wild‐type strain were turbid with little precipitate (Fig.…”
Section: Resultsmentioning
confidence: 99%